ASPEK HUKUM PEMERINTAHAN TERHADAP PENGGUNAAN TENAGA KERJA ASING DI INDONESIA DAN IMPLIKASINYA TERHADAP KEDAULATAN NEGARA - Dodi jaya wardana (Jurnal Justiciabelen, 2018)
The effectiveness and urgency of the use of foreign workers in Indonesia is very effective and urgent to meet the needs of skilled and professional workforce in certain fields that can not be occupied by local workers and as a step in accelerating the process of national and regional development by accelerating the transfer of knowledge and technology and increase foreign investment in the presence of foreign workers as supporting development in Indonesia, although in reality companies in Indonesia, whether foreign or national private companies, must use the Indonesian experts themselves. The purpose of regulating foreign workers if viewed from the aspect of labor law is basically to guarantee and provide decent employment opportunities for Indonesian citizens in various fields and levels. So that in hiring foreign workers in Indonesia must be done through strict mechanisms and procedures starting with the selection and licensing procedures to supervision